A comparative study to show the improvement in quality of life by short-term and long-term meditation by raj yoga meditation to reduce stress - Rastogi, Shalini; Kumar, Raj; Hussain, Md Sabir; Rastogi, Vichal (International journal of health sciences, 2022)
Background: Meditation brings certain biochemical and physical changes in the body namely changes in metabolism, heart rate, respiration, blood pressure and brain chemistry, collectively referred to as the ‘relaxation response. The present study was carried out to compare the improvement in quality of life by short term and long-term meditation by raj yoga meditation to reduce stress. Materials & Methods: 120 patients suffering from stress aged 18–50 years were included in the study. The patients suffering from stress were randomized to divide into two groups: Group I i.e. short term meditation by raj yoga meditation and Group II i.e. long term meditation by raj yoga meditation. Complete clinical examination, including general and systemic examination was done. Health-related quality of life (HRQOL) questions were rated. Data was collected and analysed by SPSS 22.P values of less than 0.05 was concerned significant.